Keine Empfehlung für VBI Tests - Vielitz, Arne (MSK – Muskuloskelettale Physiotherapie, 2021)
Hutting N, Kranenburg HAR, Kerry R. Yes, We Should Abandon Pre-Treatment Positional Testing of the Cervical Spine. Musculoskelet Sci Pract 2020; 49: 102181.